Social and Health-related Changes in Hispanic Cancer Patients during the COVID-19 Lockdown - Rosario-Ramos, Lianel; Peña-Vargas, Cristina; Torres-Blasco, Normarie; Rodríguez, Zindie; Tollinchi, Nelmit Natali; Hernández, Ruthmarie; Irizarry, Alexander; Pereira, Cristina; Armaiz-Peña, Guillermo N.; Castro-Figueroa, Eida M. (Puerto Rico Health Sciences Journal, 2024)
Objective: The current study aimed to explore changes in health-related behaviors and social practices in Hispanic cancer patients during a government-mandated lockdown and their relationship to sociodemographic and clinical characteristics. Methods: Secondary analyses were conducted on data gathered by a longitudinal cohort study to describe the unmet needs of Hispanic cancer patients living in Puerto Rico exposed to Hurricane Maria in 2017, earthquakes in 2020, and COVID-19. However, our study solely focuses on the data from the COVID-19 pandemic period. Results: Most participants were women (n = 72) with breast cancer (81.2%). Participants exhibited changes in religious practices (60%), physical activity (58.4%), and sedentary behavior (50%); 31.4% experienced changes in eating habits and sleeping patterns. Responses to the study questionnaire involved staying connected with family (85.5%) through phone calls (78.2%); 69.9% of the participants reported observing shifts in the family dynamics. A strong majority endorsed the government-imposed isolation measures (95.6%). Patients not undergoing treatment were likelier (r = -0.324; P = .010) to support the measures. Finally, younger patients experienced more work-related changes (r = -0.288; P = .017) and were less inclined (r = -0.293; P = .011) to find the isolation measures appropriate. Conclusion: This paper describes the lockdown related changes in health and social behaviors sustained by cancer patients, changes which could potentially impact their overall health and health-related quality of life. Our results fill an existing gap in our findings and contribute to understanding the experiences of cancer patients (in particular, Hispanic patients) during the COVID-19 pandemic.